The fate of sulfate in chronic heart failure - Koning, Anne M. (Am J Physiol Heart Circ Physiol, 2017)
New leads to advance our understanding of heart failure (HF) pathophysiology are urgently needed. Previous studies have linked urinary sulfate excretion to a favorable cardiovascular risk profile. Sulfate is not only the end product of hydrogen sulfide metabolism but is also directly involved in various (patho)physiological processes, provoking scientific interest in its renal handling. This study investigates sulfate clearance in chronic HF (CHF) patients and healthy individuals and considers its relationship with disease outcome. Parameters related to renal sulfate handling were determined in and compared between 96 previously characterized CHF patients and sex-matched healthy individuals. Among patients, sulfate clearance was analyzed for associations with clinical and outcome parameters. In CHF patients, plasma sulfate concentrations are significantly higher, whereas 24-h urinary excretion, fractional excretion, and clearance of sulfate are significantly lower, compared with healthy individuals. Among patients, sulfate clearance is independently associated with diuretics use, creatinine clearance and 24-h urinary sodium excretion. Sulfate clearance is associated with favorable disease outcome [hazard ratio per SD increase 0.38 (95% confidence interval 0.23–0.63), P < 0.001]. Although significance was lost after adjustment for creatinine clearance, the decrease of sulfate clearance in patients is independent of this parameter, indicating that sulfate clearance is not merely a reflection of renal function. This exploratory study reveals aberrant sulfate clearance as a potential contributor to CHF pathophysiology, with reduced levels in patients and a positive association with favorable disease outcome. Further research is needed to unravel the nature of its involvement and to determine its potential as a biomarker and target for therapy. NEW & NOTEWORTHY Sulfate clearance is decreased in chronic heart failure patients compared with healthy individuals. Among patients, sulfate clearance is positively associated with favorable disease outcome, i.e., a decreased rehospitalization rate and increased patient survival. Hence, decreased sulfate clearance may be involved in the pathophysiology of heart failure.